Plants diversity at the mountain forest of Waworete, East Wawonii District, Wawonii Island, Southeast Sulawesi - SITI SUNARTI; ARIEF HIDAYAT; RUGAYAH RUGAYAH (Society for Indonesian Biodiversity, 2008)
Inventory and exploration series in Wawonii island have been conducted since 2003-2006, to discover of its biodiversity. The thirds time of field work (2005) was plotted in Waworete Mountain, where located at the center of this island, include in East Wawonii District, Konawe Regency, Southeast Sulawesi Province, at the geographic positions of S 04Âº 06Â´ 843â€, E 123Âº 08Â´ 953â€. The forest still in undisturbs condition, so that, it need to be conserved. Approximately 208 plant species were identified, several species of them are new information.Anoectochilus setaceus (Bl.) Lindl., Diplocaulobium brevicole J.J.Sm. (Orchidaceae), Cyrtochloa cf. toppingii (Gamble) S. Dransf. (Poaceae) are a new record for Sulawesi and Indonesia respectively.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Waworete, Wawonii, Southeast Sulawesi, species diversity, forest.